The basic business library : core resources and services - Forte, Eric J., 1967-; Oppenheim, Michael R. (Libraries Unlimited, 2012)
"This succinct, comprehensive sourcebook provides everything needed to start, maintain, and provide service for a business collection, and to research virtually any business topic."--Resumé vydavatele